Current Status and Progress in Stem Cell Therapy for Intracerebral Hemorrhage - Ning Ding; Ran Luo; Qian Zhang; Huanhuan Li; Shuixian Zhang; Huanran Chen; Rong Hu (Translational Stroke Research, 2025)

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease - Yu Chen; Li Ma; Shuo Yang; Jan-Karl Burkhardt; Junlin Lu; Xun Ye; Weijian Jiang; Zeguang Ren; Rong Wang; Xiaolin Chen; Yuanli Zhao (Translational Stroke Research, 2020)
The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up. The MTT defined as the blood transit time between the end of cervical portion (C1) and the C7 segment of ICA. The clinical prognosis was assessed with Matsushima grading system, moyamoya vessel reduction system, and modified Rankin Scale (mRS). The correlation between hemodynamic parameter and prognosis was analyzed. Subgroup analysis was conducted between different presentations and different ages. Fifty-one patients were identified and the mean imaging follow-up interval was 5.5 months. The ICA-MTT was increased after the combined revascularization ( P < 0.001) compared with contralateral ICA. Faster preoperative ICA-MTT was significantly associated with improved mRS in the ischemic group ( P = 0.05). The increased ICA-MTT was significantly associated with favorable neoangiogenesis ( P = 0.04), moyamoya vessel reduction (> 50%) ( P = 0.023), and improved mRS score ( P = 0.008). In subgroup analysis, the correlation in the ischemic subgroup and adult subgroup remained significant. In this cohort, the ICA-MTT increased after the combined EC-IC bypass, and there was a positive correlation between the increased blood transit time and favorable outcomes. Color-coding DSA proved to be useful as a quantitative and serial method to monitor postoperative courses after revascularization in MMD.